A Time Resolved Study of Precoated AISI 441 for SOFC Interconnects Using STEM-EELS - Part II. (2nd June 2015) - Karlsson, Lisa S; Lundberg, Mats W; Berger, Robert; Westlinder, Jörgen
Abstract : Precoated AISI441 for SOFC interconnectors were investigated by STEM-EELS looking at the diffusion processes in the initial stage of the oxidation. The electron beam physical vapour deposition (EB-PVD) coating contained Ce and Co/Mn-alloy in two layers with at total thickness of 800 nm. The samples were exposed up to 1000 hours at 800°C, and then characterized by STEM-EELS. Multiple linear least squares (MLLS) fitting of reference spectra aids the interpretation of the elemental maps due to overlapping edges. Within 4 min heat treatment the oxidation front has reached the substrate steel and Cr2 O3 is forming at the stainless steel interface. CeO2 acts as the barrier line for Cr and is situated between the Cr-containing spinels and the (Co, Mn)-spinel after up to 168 h heat treatment.